Building Positive Society on Leading Program of Nusa Tenggara Barat at Covid-19 - Najamuddin Amy (Airlangga Development Journal, 2021)
In 2020, elements of a country such as government, society, entrepreneurs have experienceddifficulties due to the effects of the covid-19 virus. The effects of the co-19 pandemic not only attackhealth aspects, but also education, economy, welfare and defense. Provinsi Nusa Tenggara Barat withthe vision of NTB Gemilang has a goal to realize NTB as a pleasant place to live. The goal of NTBGemilang is to create a competent society, tough, virtuous and government bureaucracy oriented topublic services. But, the ideals of NTB Gemilang are constrained by the emergence of a Covid-19pandemic. Over time, covid-19 has begun to be controlled. Health facilities have started to be quiteadequate. Some policies for covid-19 control have been adopted. The government is trying to rebuildpublic expectations of leading programs in order to realize the vision of NTB Gemilang.